Pengaruh Kepemilikan Asing terhadap Nilai Perusahaan - Ramadhani, Arum; Andayani, Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Firm value is a measure of a business's performance that is derived from supply and demand dynamics in the stock market and is reflected in the stock price. Good corporate performance is reflected in a high firm value, and foreign ownership is one aspect that influences firm worth. Using a sample of primary consumer goods sector companies listed on the IDX from 2017 to 2022, this study seeks to ascertain the effect of foreign ownership on firm value, as assessed by Tobin's Q. The hypothesis is tested using a simple linear regression analysis, and the findings demonstrate that foreign ownership positively affects Tobin's Q, a measure of firm value. This study suggests that in addition to concentrating on financial conditions, businesses need take other aspects into account in order to retain the stability of their value.